Lifestyle modification factors in hypertensive patients: impact on blood pressure variability - N. Ya. Dotsenko; S. S. Boev; I. A. Shekhunova; L. V. Нerasуmenko; A. V. Molodan; A. Ya. Malinovskaya (Сучасні медичні технології)
Current guidelines do not suggest considering blood pressure variability in the management of hypertensive patients. At the same time, a sufficient evidence base has been accumulated on the relationship of blood pressure variability with damage to target organs, the development of stroke, myocardial infarction, cardiovascular mortality, and kidney disease. In general, assessing the effect of blood pressure variability on the course of arterial hypertension, it can be assumed that it is not as significant as the absolute values of blood pressure, but this effect has been proven, regardless of the degree of hypertension. And if a practitioner finds an increased variability in blood pressure in his patient, he should know what recommendations should be given to him.